ORGANIZING ADULT SPORTS IN THE FAMILY (Scientific journal of the Fergana State University, 2023)
This article discusses the importance of physical education and sports in maintaining good health and longevity, especially from infancy to adulthood. The author emphasizes the need for regular physical activity, which is often neglected by people as they age and become busier with lifeʼs worries. The article suggests that physical education and sports can be continued in the family by creating conditions for independent exercise and organizing team competitions with family and neighborhood children. The author provides examples of various sports and exercises that can be done at home, including running, jumping, cycling, swimming, and gym workouts. Finally, the article highlights the significance of morning exercise in preparing the body for work, calming the nerves, and maintaining a healthy body weight.